2018
DOI: 10.1101/399972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactivated spatial context guides episodic recall

Abstract: 25The medial temporal lobe (MTL) is known as the locus of spatial coding and episodic memory, 26 but the interaction between these cognitive domains, as well as the extent to which they rely on 27 common neurophysiological mechanisms is poorly understood. Here, we use a hybrid spatial-28 episodic memory task to determine how spatial information is dynamically reactivated in sub-29 regions of the MTL and how this reactivation guides recall of episodic information. Our results 30 implicate theta oscillations acr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…In the fMRI literature, it has been shown that hippocampal activity encodes for spatial (63) and abstract representational distances (64) and that hexadirectional modulation of the BOLD signal is observed during mental travel through abstract or imagined spaces (65,66). Several recent studies have suggested that theta power may itself correlate with spatial distances (14,16,17), just as we showed a correlation between theta and representational distances in this paper. If free recall truly constitutes a form of navigation through a semantic-temporal space, might we observe hexadirectionally modulated theta during episodic retrieval?…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In the fMRI literature, it has been shown that hippocampal activity encodes for spatial (63) and abstract representational distances (64) and that hexadirectional modulation of the BOLD signal is observed during mental travel through abstract or imagined spaces (65,66). Several recent studies have suggested that theta power may itself correlate with spatial distances (14,16,17), just as we showed a correlation between theta and representational distances in this paper. If free recall truly constitutes a form of navigation through a semantic-temporal space, might we observe hexadirectionally modulated theta during episodic retrieval?…”
Section: Discussionsupporting
confidence: 76%
“…Hippocampal theta has been associated with spatial navigation in rodents (see ref. 57 for a review) and humans (14)(15)(16) and is seen during spontaneous retrieval of information encountered in a spatial layout (17). Findings during nonspatial memory tasks have been decidedly more mixed, with many studies showing a decrease in MTL theta power during encoding and retrieval (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations